Peran Pustakawan dalam Pelestarian Koleksi di Perpustakaan SMK Negeri 1 Bandar Lampung - Purwanto Putra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2022)
Librarians have the duty and responsibility to carry out library management and services, not only services but also play an important role in the preservation of library materials. Librarians must be able to elaborate on the need for preservation of library materials and identify various factors causing damage and efforts to maintain library materials. Therefore, it is important to see the role of librarians in preserving collections in the Library of SMK Negeri 1 Bandar Lampung. This study uses a qualitative method with the aim of knowing the role of librarians in preservation activities, through various activities carried out, along with the obstacles faced by librarians. Data collection techniques in this study is to conduct interviews and observations. The findings are 1.) the role of the manager in preservation is to take preventive measures such as physical collection of books, both old and new collections, and cleaning infrastructure such as bookshelves regularly 2.) preservation activities have been carried out since the library was established, marked by repair various collections with the type of damage in the light category. 3. There is no further preservation effort for preservation and there is no special room for preservation so that the repair process cannot run optimally.